The energy potential of some hypothetical nitrosubstituted tetrazoles derivatives - I. Yu. Gudkova; D. B. Lempert (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The energy abilities of solid composite propellants based on some nitrosubstituted tetrazole derivatives, which are still hypothetical but they are promising for create on their basis rather powerful propellants, have been considered. It is confirmed by the thermodynamic calculations